The use of data for health and welfare management of farmed salmons in Norway, Scotland, and Ireland - Xiao Zhou; Annette S. Boerlage; Britt Bang Jensen; Kristine Gismervik; Victor H.S. Oliveira; Ian Hutchinson; Alison Burrell; David A. Graham; Charlotte Doidge; Jasmeet Kaler; Gerdien van Schaik; Michael Siegrist; et al. (Preventive Veterinary Medicine, 2025)

The effect of arterial cannula tip position on differential hypoxemia during venoarterial extracorporeal membrane oxygenation - Avishka Wickramarachchi; Aidan J. C. Burrell; Andrew F. Stephens; Michael Šeman; Ashkan Vatani; Mehrdad Khamooshi; Jaishankar Raman; Rinaldo Bellomo; Shaun D. Gregory (Physical and Engineering Sciences in Medicine, 2023)

Annual precipitation explains variability in dryland vegetation greenness globally but not locally - Anna M. Ukkola; Martin G. De Kauwe; Michael L. Roderick; Arden Burrell; Peter Lehmann; Andy J. Pitman (Global Change Biology, 2021)
Dryland vegetation productivity is strongly modulated by water availability. As precipitation patterns and variability are altered by climate change, there is a pressing need to better understand vegetation responses to precipitation variability in these ecologically fragile regions. Here we present a global analysis of dryland sensitivity to annual precipitation variations using long‐term records of normalized difference vegetation index (NDVI). We show that while precipitation explains 66% of spatial gradients in NDVI across dryland regions, precipitation only accounts for 75%) dryland regions. We observed this weaker temporal relative to spatial relationship between NDVI and precipitation across all global drylands. We confirmed this result using three alternative water availability metrics that account for water loss to evaporation, and growing season and precipitation timing. This suggests that predicting vegetation responses to future rainfall using space‐for‐time substitution will strongly overestimate precipitation control on interannual variability in aboveground growth. We explore multiple mechanisms to explain the discrepancy between spatial and temporal responses and find contributions from multiple factors including local‐scale vegetation characteristics, climate and soil properties. Earth system models (ESMs) from the latest Coupled Model Intercomparison Project overestimate the observed vegetation sensitivity to precipitation variability up to threefold, particularly during dry years. Given projections of increasing meteorological drought, ESMs are likely to overestimate the impacts of future drought on dryland vegetation with observations suggesting that dryland vegetation is more resistant to annual precipitation variations than ESMs project.

Erratum for “Fluctuating Asymmetry and Growth as Biomarkers for Exposure to Androgen Disrupting Chemicals in Japanese Quail” [10.1007/s10646-005-0013-9(10646-2005-13 Quinn)] - Michael J. Quinn; C. L. Summitt; K. Burrell; M. A. Ottinger (Ecotoxicology, 2005)

Serological and molecular diversity in the cattle MHC class I region - Shirley A. Ellis; W. Ivan Morrison; Niall D. MacHugh; James Birch; Alison Burrells; Michael J. Stear (Immunogenetics, 2005)

Fluctuating Asymmetry and Growth as Biomarkers for Exposure to Androgen Disrupting Chemicals in Japanese Quail - MICHAEL J. C.L. SUMMITT; K. BURRELL; M.A. OTTINGER (Ecotoxicology, 2005)

Proteomic analysis reveals a novel set of cell wall proteins in a transformed tobacco cell culture that synthesises secondary walls as determined by biochemical and morphological parameters - Kristopher A. Blee; Edward R. Wheatley; Victoria A. Bonham; Geoffrey P. Mitchell; Duncan Robertson; Antoni R. Slabas; Michael M. Burrell; Przemyslaw Wojtaszek; G. Paul Bolwell (Planta, 2001)

Analysis of multiple copies of geminiviral DNA in the genome of four closely related Nicotiana species suggest a unique integration event - Mark K. Ashby; Andrew Warry; Eduardo R. Bejarano*; Alaa Khashoggi; Michael Burrell; Conrad P. Lichtenstein* (Plant Molecular Biology, 1997)